2021
DOI: 10.1016/j.psj.2020.11.067
|View full text |Cite
|
Sign up to set email alerts
|

Dietary probiotics as a strategy for improving growth performance, intestinal efficacy, immunity, and antioxidant capacity of white Pekin ducks fed with different levels of CP

Abstract: The potential impacts of probiotics on the performance and health status of white Pekin ducks fed with optimal or suboptimal dietary CP were evaluated during the growing period. A total of 180 male white Pekin ducks (14-day-old ducks with an initial weight of 415.65 ± 2.20 g) were randomly divided into 4 experimental groups (45 in each group of 5 replicates) in a 2 × 2 factorial design. The main factors included 2 dietary CP levels (18 or 14%) and dietary probiotic addition (with or without probiotics). The pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 87 publications
1
18
0
Order By: Relevance
“…Increased protein digestibility affects the improvement of protein metabolism so that it affects the increase in meat protein synthesis [43]. The results align with Khattab's study, which showed that adding probiotics L. acidophilus and L. casei in the diet showed an increase in body weight gain and final body weight and also an increase in intestinal enzyme activity (protease, lipase, and amylase), morphometric (goblet cell count, villi length, and crypt depth), and an increase in carcass percentage [45]. The mechanism of the action of probiotics is to stick or adhere to and colonize in the digestive tract, producing antimicrobial substances helping the enzymatic digestion of feed [46].…”
Section: Carcass Yield (Carcass Weight and Percentage) And Mortalitysupporting
confidence: 82%
“…Increased protein digestibility affects the improvement of protein metabolism so that it affects the increase in meat protein synthesis [43]. The results align with Khattab's study, which showed that adding probiotics L. acidophilus and L. casei in the diet showed an increase in body weight gain and final body weight and also an increase in intestinal enzyme activity (protease, lipase, and amylase), morphometric (goblet cell count, villi length, and crypt depth), and an increase in carcass percentage [45]. The mechanism of the action of probiotics is to stick or adhere to and colonize in the digestive tract, producing antimicrobial substances helping the enzymatic digestion of feed [46].…”
Section: Carcass Yield (Carcass Weight and Percentage) And Mortalitysupporting
confidence: 82%
“…However, most research about the effect of dietary administration of probiotic Bacillus strains on growth performance has been conducted in chicken, mouse, and pig [7][8][9][10], and yet only recently it was experimentally shown that certain strains of B. subtilis can provide beneficial effects on the growth of young broiler chickens and have the potential to replace antibiotic growth promoters [11] or improve egg quality [12]. Similar studies on ducks have been fewer [13,14], and we failed to find reports on gut microbiome research using probiotic Bacillus strains for Pekin ducks.…”
Section: Introductionmentioning
confidence: 99%
“…The dietary amendment exemplifies an astonishing approach to altering animals' performance and welfare (Abdel‐wanees & El Basuini, 2018; Dawood et al, 2020; Dossou et al, 2021; Khattab et al, 2021). The improvement of immune response in association with SH in the present study was in terms of enhancement in serum IgG, IgM and TNF‐α.…”
Section: Discussionmentioning
confidence: 99%
“…Poultry is among the most lucrative, fast‐growing, key economic investments that contribute to delivering superior nutrients (Khattab et al, 2021). Quail production is emerging as a prosperous poultry sector compared to other poultry species since, quail has faster sexual maturity, persistence in egg production, short generation interval and low feed and space requirements, and less susceptibility to diseases (Khaskheli, 2020).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation